Features of the Impact of Coronavirus Infection on the Gastrointestinal Tract in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The high frequency of registration of gastrointestinal disorders, in many children before the start of therapy, confirms the tropism of the new coronavirus to the gastrointestinal tract. A large number of cases of discomfort in the abdomen after eating, nausea, and flatulence indicate, probably, developing fermentopathy and possible involvement of the pancreas and hepatobiliary system in the infectious and inflammatory process, which also requires further study. This review summarizes the manifestations and potential mechanisms for the development of gastrointestinal manifestations in COVID-19 in children.